GRAIN SORGHUM - SANCHEZ D, NICOLAS; PUERTAS FABILA, JOSE LUIS; PITNER, JOHN B (Hospital General, CD MEXICO, DF, MEX, 1949)
Extensive experimentation in many of the higher valleys of Mexico during the last 5 yrs has established the feasibility of growing wheat during the summer rainy season Parts of the areas now planted to barley and oats will net the farmer a higher return
PHYS REV B
Keywords: GRAIN SORGHUM; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL; BOTANICA GENERAL